1980
DOI: 10.1007/bf01256634
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute lithium administration on conditioned avoidance behavior and monoamine synthesis in rats

Abstract: The effect of a single injection of various doses of lithium chloride was tested on conditioned avoidance behavior and on the accumulation of DOPA and 5-HTP after inhibition of aromatic amino acid decarboxylase. Lithium specifically suppressed conditioned avoidance behavior and reduced formation of DOPA, but not 5-HTP. The behavioral effect of lithium could be completely antagonized with additional L-DOPA treatment. The results indicate that lithium has a neuroleptlike effect on avoidance behavior, and it is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
2

Year Published

1981
1981
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
1
11
2
Order By: Relevance
“…Jacobsen, 1959;Borsyet al, 1960). These findings are in agreement with the contention that lithium in acute experiments has a neuroleptlike behavioural profile (see Engel and Berggren, 1980). Lithium suppressed locomotor stimulation induced by amphetamine, ethanol or morphine.…”
Section: Discussionsupporting
confidence: 91%
“…Jacobsen, 1959;Borsyet al, 1960). These findings are in agreement with the contention that lithium in acute experiments has a neuroleptlike behavioural profile (see Engel and Berggren, 1980). Lithium suppressed locomotor stimulation induced by amphetamine, ethanol or morphine.…”
Section: Discussionsupporting
confidence: 91%
“…This finding suggests that the decreased synthesis of 5-HT in lithiumtreated rats is not due to shortage of substrate but rather to other mechanisms, such as lithium-induced decrease of the activity of tryptophan hydroxylase, which has been described by Mandell and Knapp (1976). In our earlier work, Berggren et al (1980), we found no effect on 5-HT synthesis in the limbic forebrain or the striatum following acute lithium administration of approximately the same dose as given in the present work, indicating that the decreased 5-HT synthesis occurs in other brain regions. Furthermore acute lithium administration appears to affect 5-HT synthesis to a greater extent than it affects catecholamine synthesis.…”
Section: Discussioncontrasting
confidence: 64%
“…However, since manipulations with the precursor amino acids tyrosine and tryptophan in animals have been shown to affect brain catecholamine synthesis and 5-HT synthesis respectively (Carlsson and Lindwist, 1978) some reports suggest that lithium may affect brain monoamine synthesis in animals via its efect an brain tyrosine (Berggren et aL, 1980) and brain tryptophan levels (Perez-Cruet et al, 1971;Schubert, 1973).…”
Section: Introductionmentioning
confidence: 97%
“…Segal et al [1975] found an increase in striatal tyrosine hydroxylase activity following 8 days of Li treatment. In contrast, Friedman and Gershon [1973] noted a decrease in striatal DA synthesis after 14 days of Li treatment, while Berggren et al [1980] demonstrated a decrease in dopa accumulation following treatment with an aromatic amino acid decarboxylase inhibitor after acute Li administration. Both the present data and those previously reported [Ahluwalia and Singhal.…”
Section: Discussionmentioning
confidence: 77%